1966
DOI: 10.1287/mnsc.12.7.609
|View full text |Cite
|
Sign up to set email alerts
|

On Some Properties of Programming Problems in Parametric form Pertaining to Fractional Programming

Abstract: This paper presents results which apply to convex programming problem in parametric form. The results secured are also related to the problem of fractional programming in a way which indicates computational possibilities for the latter class of problems. The results are extended to general non-linear programming problems with special reference to continuous criterion functions. As a particular case, the linear fractional programming problem is considered and, in conclusion, the results secured here are pointed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(65 citation statements)
references
References 9 publications
1
64
0
Order By: Relevance
“…Then, since all the constraint functions in (37) and (38) are monotonic and continuous, by virtue of Proposition 2 and employing again (35), it follows that S and S c are normal and co-normal sets in the hyper-rectangle given by:…”
Section: Global Optimality: Monotonic Fractional Programmingmentioning
confidence: 99%
“…Then, since all the constraint functions in (37) and (38) are monotonic and continuous, by virtue of Proposition 2 and employing again (35), it follows that S and S c are normal and co-normal sets in the hyper-rectangle given by:…”
Section: Global Optimality: Monotonic Fractional Programmingmentioning
confidence: 99%
“…Problem (4) is a max-min fractional program, for which a common approach is based on solving a parametric program and a two-layer iterative procedure, i.e., a Dinkelbach-type algorithm [9], [10]. As numerically shown in Sect.…”
Section: Proposed Low-complexity Beamforming Designmentioning
confidence: 99%
“…Thus, the convergence of the alternating maximization of steps 3-5 in Algorithm 3 can be guaranteed with the monotonic convergence theorem [41]. In the results obtained in [15,39,40], one can see that the convergence of Algorithm 3 is also guaranteed. In particular, based on the conclusion given by [41,Prop.…”
Section: Algorithm Designmentioning
confidence: 87%
“…It is easy to see that problem (28) belongs to a classical fractional programming problem. In addition, the works in [15,39,40] have shown that it is equivalent to looking up a value of α such that the optimal objective value of the following optimization problem (29) equals to zero.…”
Section: Algorithm Designmentioning
confidence: 99%
See 1 more Smart Citation